Analyzing the Long-Term Effects of Eliminating School Fees on Access to and Quality of Education in Uganda, Considering the Policy's Implications for Gender Parity and Inclusive Education - Kiyingi, Samuel (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to analyze the long-term effects of eliminating school fees on access to and quality of education in Uganda, considering the policy's implications for gender parity and inclusive education. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The elimination of school fees in Uganda under the Universal Primary Education (UPE) policy has significantly increased access to education, particularly for children from low-income families and marginalized communities, as seen in the surge in enrollment rates. However, this increase in access has not been matched by improvements in educational quality, with overcrowded classrooms, underqualified teachers, and inadequate resources affecting learning outcomes. Unique Contribution to Theory, Practice and Policy: Human capital theory, capability approach & social justice theory may be used to anchor future studies on the analyzing the long-term effects of eliminating school fees on access to and quality of education in Uganda, considering the policy's implications for gender parity and inclusive education. Special focus should be on training teachers in inclusive education to better support children with disabilities and gender-sensitive teaching methods that encourage the retention of girls in school. Policies should ensure free provision of essential materials, especially for the most vulnerable populations.